Effect of Exposure to PM10 on Cardiovascular Diseases Hospitalizations in Ahvaz, Khorramabad and Ilam, Iran During 2014 - Seyed Mohammad Daryanoosh; Gholamreza Goudarzi; Yusef Omidi Khaniabadi; Houshang Armin; Hassan Bassiri; Fatemeh Omidi Khaniabadi (Iranian Journal of Health, Safety and Environment, 2016)
Particulate matter with an aerodynamic diameter less than or equal to 10μm (PM10) has the great adverse endpoints on human health. The aim of this study was to assess the hospital admissions (HA) due to cardiovascular diseases (CVD) attributed to PM10 among people living in the cities of Ahvaz, Khorramabad and Ilam, during 2014. In this study, Air Quality Health Impact Assessment (AirQ2.2.3) software proposed by the World Health Organization (WHO) to assess of health impacts of atmospheric pollutants was used. To evaluate human exposure and health outcome of PM10, 24-hour data was taken from the Departments of Environment of Ahvaz, Khorramabad and Ilam. We acquired an input file for the software from raw data and quantified PM10 by the AirQ2.2.3 model. The annual averages in three study areas illustrated that PM10 concentration in Ahvaz and Ilam with values of 534.77 and 60.45μg/m3, were the highest and lowest in 2014, respectively. The number of excess cases for HA due to CVD in Ahvaz, Khorramabad, and Ilam was estimated 508, 144 and 66 persons, respectively. The most percentage of person-days was attributable to the concentration interval of 130-139µg/m3 of PM10, whereas this was for Khorramabad and Ilam 60-69 and 40-49µg/m3, respectively. The comparison of PM10 concentrations with NAAQS standard was revealed the annual average of particulate matter concentrations in Ahvaz was higher than standard. Therefore, the efforts should be conducted in the governmental scale to prevent pollution and reduce PM10 emission from various sources, such as transport and industries and also control dust entering the country by spreading mulch and development of green space.